Quantum criticality of excitonic Mott metal-insulator transitions in black phosphorus - Binjie Zheng; Junzhuan Wang; Qianghua Wang; Xin Su; Tianye Huang; Songlin Li; Fengqiu Wang; Yi Shi; Xiaomu Wang (Nature Communications, 2022)
The exciton Mott transition refers to a transition from an insulating state of gas-like excitons to strongly correlated electron-hole plasma phases in photoexcited semiconductors. Here the authors experimentally study such a transition in black phosphorus and reveal its quantum critical properties.